Survivability and ejection injury pattern in Bangladesh Air Force fighter crew: a 30 years study from 1982-2012 (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Fighter flying is one of the most hazardous occupations known to man. Emergency escape from the aircraft is an important issue to ensure the safety and survivability of aircrew. In spite of advancement of ejection system, both rate and severity of injuries sustained during ejection remain a cause for concern. Objectives: The purpose of this study was to assess the number of survivability, causes of death in fatal cases, patterns of ejection injuries among the aircrews of Bangladesh Air Force (BAF) and to find out the ways to minimize the fatality and injuries during escape from disabled aircraft. Methods: This descriptive case series study was conducted at the BAF flight safety directorate and Combined Military Hospital (CMH), Dhaka among the aircrews of Bangladesh Air Force fighter planes which were crashed during the period of 1982 to 2012. The records of injuries, medical documents during admission at hospital, radiological and laboratory investigations reports, clinical analysis of pilots were utilized for this paper. Post mortem reports of fatal cases were also carefully considered. Results: Out of 23 ejection cases 10(43.48 %) were fatal and 13(56.52%) cases were non fatal. All the pilots (100%) had multiple abrasions, bruises, lacerations in their body. Penetrating injury was observed in one case (10%), one (10%) body was totally mutilated and 06(60%) showed burn injury. All the pilots had thoracic spine compression fracture (100%), 8(80%) had cervical hangmans fracture and lumbar spine fracture. Seven victims (70%) had ruptured diaphragm, 6(60%) had ruptured liver, 5(50%) had ruptured spleen, 2(20%) pilots had ruptured kidneys and urinary bladder. All the pilots (100%) had fracture of lower limbs, 8(80%) had fractured upper limbs. Among the non fatal cases all the pilots (100%) had multiple abrasions, bruises, 6 (46.15%) had laceration, 01 (7.69%) each sustained anterior cruciate ligament tear of knee joint (Lt) and fracture middle of the shaft of the humerus (Lt). The mean age of the pilots was 31yrs (24 41 yrs). Conclusion: Protective measures and training among aircrews should be updated, so that less injury occurs in survivors. Thorough medical diagnosis and psychological treatment are required for the injured aircrews.DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21861 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013